Enhancing Water Quality: Application of Coconut Shell Activated Charcoal for Sulfide and Ammonia Removal from Tofu Industry Wastewater - Asnawati, Asnawati; Novita Andarini; Mulyono, Tri; Maimunah Noer Aini; Nur Fitriyah; Siswoyo; Zulfikar; Yeni Maulidah Muflihah (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
This study investigates the optimization of an adsorption process using activated coconut shell charcoal to reduce sulfide and ammonia levels in tofu industry wastewater. These pollutants pose significant environmental risks due to their biodegradable nature. Experimental parameters, including adsorbent particle size (50, 60, and 70 mesh), heating temperature (40, 80, 120 °C, and ambient), and contact time (15-60 minutes for sulfide, 20-100 minutes for ammonia), were systematically varied to determine optimal conditions. The initial sulfide and ammonia concentrations in the wastewater exceeded regulatory limits at 0.169 mg/L and 8.177 ppm, respectively. The results indicate that 70-mesh activated charcoal at ambient temperature achieved maximum pollutant removal: 93.46% for sulfide with a 30-minute contact time and 93.693% for ammonia with a 40-minute contact time. These findings offer a promising approach to mitigating the environmental impact of tofu industry wastewater.